The Projection of the Belt and Road Initiative into the European Union (2014-2019): Economic and Normative Implications - Rocha Pino, Manuel de Jesús (2020)
This research analyzes the characteristics of the projects of the Belt and Road Initiative (BRI) implemented during the period 2014-2019 in the European Union (EU), and their relevance for the development of Sino-European political and economic relations. This process has been developed in a context of increasing economic interdependence between the actors, something evidenced by the high volumes reached in their commercial exchanges. The research uses an approach based on the liberal-institutionalism theory in order to analyze the preferences chosen by China and the EU to guide their relationship in a pragmatic way, although not without asymmetries, as well as the institutional instruments used to coordinate the bilateral agenda: the institutional platform having the coordinating function of the BRI activities in the EU is the China-EU strategic partnership. Some of the conclusions identified in the research are: 1) the EU is considered by the Chinese government as a fundamental region for the implementation of the BRI; 2) the investing in infrastructure projects financed by Chinese capital has the objective of deepening economic interdependence with EU members, and 3) the Chinese government must take into account the economic interests of the European part and respect for EU regulations.